THE CLIL APPROACH IN TEACHING ENGLISH TO RAILWAT STUDENTS: EXPERIENCE OF KOKAND RAILWAY TECHNICAL COLLAGE (Лучшие интеллектуальные исследования, 2025)
Abstract: This article is devoted to the implementation of the CLIL (Content and Language Integrated Learning) methodology in teaching English to railway students. It describes the experience of Kokand Railway Technical School in integrating specialized disciplines (e.g., "Station Duty Planning") with English language instruction. The article analyzes methodological solutions, presents the results of a pilot course, and outlines the prospects for further development.